Risk factors for postoperative delirium after elective major abdominal surgery in elderly patients: A cohort study. (November 2019) - Janssen, T.L.; Steyerberg, E.W.; Faes, M.C.; Wijsman, J.H.; Gobardhan, P.D.; Ho, G.H.; van der Laan, L.
Abstract: Background: Prehabilitation programs have recently been suggested as potentially able to lower the incidence of delirium in elderly patients undergoing major abdominal surgery. For these prehabilitation programs to become successful, it is essential to identify those patients who are most likely to develop a delirium. Material and methods: A single-centre cohort study was conducted. Inclusion criteria were: age ≥70 years and scheduled for abdominal surgery for colorectal cancer or an abdominal aortic aneurysm between January 2013 and June 2018. Baseline patient, surgical, anaesthesiologic and haematological characteristics were collected. A risk factor analysis was conducted, with postoperative delirium as primary outcome, by performing a multivariable logistic regression analysis. Results: In this study, 627 patients were included, of whom 64 (10%) developed a delirium. Variables that differed significantly between delirious and non-delirious patients were age, burden of comorbidity, renal impairment, hypertension, cognitive impairment, history of delirium, physical and nutritional impairment, open surgery, preoperative anaemia and erythrocyte transfusion. After multivariable logistic regression analysis, risk factors for postoperative delirium after major abdominal surgery were renal impairment (OR 2.2; 95%CI 1.2–4.3), cognitive impairment (OR 4.1; 95%CI 1.8–9.2), an ASA score ≥ 3 (OR 2.0; 95% CI 1.0–3.9), being an active smoker (OR 2.7; 95%CI 1.3–5.8), ICU admission (OR 7.1; 95%CI 3.5–14.3), erythrocyte transfusion (OR 2.4; 95%CI 1.2–4.9) and a diagnosis of colorectal cancer (CRC); (OR 4.0; 95% CI 1.7–9.6). Prehabilitation had a protective effect (OR 0.5; 95% CI 0.3–0.9). Conclusion: Postoperative delirium is a frequent complication after major abdominal surgery in the elderly, especially in octogenarians and after open procedures. Renal impairment, cognitive impairment, being an active smoker, ICU admission, erythrocyte transfusion and a diagnosis of CRC are important risk factors for the development of delirium. Prehabilitation lowers the risk of developing a delirium. Highlights: The increasing number of elderly patients requires new methods to prevent postoperative delirium. Identification of the patients who are most at risk for developing delirium is therefore imperative. Risk factors for delirium are renal or cognitive impairment, ASA≥3, being an active smoker, ICU admission and erythrocyte transfusion. Prehabilitation has a protective effect, however may not be worthwhile prior to endovascular aortic repair. Future prehabilitation programs on delirium prevention should incorporate smoking cessation and haemoglobin optimisation.